1998
DOI: 10.1101/gad.12.7.996
|View full text |Cite
|
Sign up to set email alerts
|

A coactivator of pre-mRNA splicing

Abstract: The nuclear matrix antigen recognized by the monoclonal antibody (mAb) B1C8 is a novel serine (S) and arginine (R)-rich protein associated with splicing complexes and is named here SRm160 (SR-related matrix protein of 160 kD). SRm160 contains multiple SR repeats, but unlike proteins of the SR family of splicing factors, lacks an RNA recognition motif. SRm160 and a related protein SRm300 (the 300-kD nuclear matrix antigen recognized by mAb B4A11) form a complex that is required for the splicing of specific pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
223
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(237 citation statements)
references
References 63 publications
12
223
0
2
Order By: Relevance
“…Recent studies have suggested that a coactivator(s) of pre-mRNA splicing in nuclear extracts is necessary for adequate splicing activity (Blencowe et al 1998).…”
Section: Expression Of Recombinant Nssr 1 and 2 And The Generation Omentioning
confidence: 99%
“…Recent studies have suggested that a coactivator(s) of pre-mRNA splicing in nuclear extracts is necessary for adequate splicing activity (Blencowe et al 1998).…”
Section: Expression Of Recombinant Nssr 1 and 2 And The Generation Omentioning
confidence: 99%
“…Two strong candidates for factors that might couple splicing components are Ser-Arg (SR)-related matrix protein of 160 kDa (SRm160) and SR-related matrix protein of 300 kDa (SRm300), two high molecular mass SR-related proteins (11)(12)(13)(14)(15). These proteins are bound more tightly to the nuclear matrix than other SR proteins, are binding partners, and are constituents of in vitro-assembled spliceosomes.…”
mentioning
confidence: 99%
“…We suggest that SRm160 and SRm300 are key players in the recruitment of splicing factors to sites of splicing and in the assembly of presplicing complexes on the nuclear matrix, contributing to the greater efficiency of splicing in intact nuclei. Although both proteins participate in splicing reactions, SRm160 may be the more important for in vitro splicing, being required for the splicing of some RNA substrates (13,14). …”
mentioning
confidence: 99%
“…However, the nuclear speckles observed from SRC-1 and the round granules observed from SRC-2 and SRC-3 are morphologically similar to discrete subnuclear compartments that are associated with specific nuclear activities such as mRNA synthesis, pre-mRNA splicing [38,39,40]. Splicing factors such as SC-35 and SRm160 are primarily localized to nuclear foci referred to as splicing speckles or nuclear speckles [41,42]. Consistent with our observations, SRC-2/GRIP1 and SRC-3 have been found to associate with ND10 bodies, a small nuclear substructure containing several proteins that are implicated in the regulation of transcription, apoptosis, tumor suppression and the anti-viral response [43].…”
Section: Discussionmentioning
confidence: 90%